Methods for describing the shape of defective nanostructured formations in materials under irradiation - Kul’ment’ev, A.I. (Вопросы атомной науки и техники, 2019)
Within the framework of the program of using modern computer methods in the task of developing radiation-resistant materials for IV-generation reactors, several methods for describing the form of local atomic segregations or compact radiation defects of the nanometer range have been considered. A numerical method for measuring the shape of an arbitrary atomic formation possessing a well-defined external boundary is proposed. The shape of the sequence of equilibrium clusters is measured, the interaction of the particles in which is described by the Lennard-Jones potential. It is shown that the proposed method correctly reproduces the oscillations of size effects and the sequence of magic numbers for these clusters. The possibility of replacing geometric moments by the moments of Zernike 3D functions is considered. Such a replacement allows us to get rid of the ill-posed nature of the inverse problem in the transition from the source space of clusters form to the space of their descriptors. У рамках програми використання сучасних комп'ютерних методів у завданнi розробки радіаційно стійких матеріалів для реакторів IV покоління розглянуто кілька методів опису форми локальних атомних сегрегації або компактних радіаційних дефектів нанометрового діапазону. Запропоновано чисельний метод вимірювання форми довільного атомного утворення, що має добре визначену зовнішню межу. Виконано вимір форми послідовності рівноважних кластерів, взаємодія частинок в яких описується потенціалом Леннард-Джонса. У запропонованому методі коректно відтворюються осциляції розмірних ефектів та послідовність магічних чисел для цих кластерів. Розглянуто можливість заміни геометричних моментів на моменти 3D-функцій Цернике. Така заміна дозволяє позбутися від некорректного характеру оберненої задачі при переході від початкового простору форм у простір їх дескрипторів. В рамках программы использования современных компьютерных методов в задаче разработки радиационно стойких материалов для реакторов IV поколения рассмотрены несколько методов описания формы локальных атомных сегрегаций или компактных радиационных дефектов нанометрового диапазона. Предложен численный метод измерения формы произвольного атомного образования, обладающего хорошо определенной внешней границей. Выполнено измерение формы последовательности равновесных кластеров, взаимодействие частиц в которых описывается потенциалом Леннард-Джонса. В предложенном методе корректно воспроизводятся осцилляции размерных эффектов и последовательность магических чисел для этих кластеров. Рассмотрена возможность замены геометрических моментов на моменты 3D-функций Цернике. Такая замена позволяет избавиться от некорректного характера обратной задачи при переходе от исходного пространства форм в пространство их дескрипторов.